REGIONS IN INTERNATIONAL POLITICS: A FRAMEWORK FOR INTEGRATING SYSTEMIC, REGIONAL, DYADIC, AND MONADIC APPROACHES - T. J. Volgy; J. P. Rhamey, Jr. (Vestnik MGIMO-Universiteta)
The article proposes the framework of further analysis of regional political processes. The authors believe that the significant amount of activities is occurring on the regional level. Thus, the moderate aim of the article is to link different levels of analysis and to present measurable variable to explore regional political developments in this context. The basic assumption of the article is that there are more hierarchical relationships on the regional level than on the global one. Regional powers objective try to create security and stability in their regional areas which increases the overall stability. However, some regions are lacking conditions for durable hierarchy, which is a structural reason for instability and conflicts. The problem the latter regions face is their limited chance of creating durable structures of cooperation, because hierarchy implies some structural violence that helps to realize interests and understand policy limitations. The article presents comparative framework that assesses features of regional powers such as strength or weakness, absence of rivals or their presence. The framework also includes state’s policies that may disregard the regional context in order to seek more promising opportunities. The “hierarchy and interest”- based analysis demonstrates that some regions have strong spatial appearance while the others are only in search of their spatial identity. This allows elaborating on the dependent variables such as territorial disputes, cooperation of rivals, political regime performance. The authors conclude that the presented framework can be useful for further analysis and enriches potential for testing hypotheses of regional political behavior of state actors.